Evaluation of Spatial Plan Policy on Minimarket Arrangement in Surabaya - Bachrul Amiq; Moh Taufik; Renda Aranggraeni (Global Writing Academica Researching & Publishing, 2023)
This research was motivated by the growth of modern stores in the city of Surabaya which can increasingly be seen in everyday life. Minimarket as one type of modern store in the city of Surabaya. Even according to the Surabaya City Spatial Planning Office in 2014 there were 488 minimarkets with retail status spread across 31 districts in the city of Surabaya. The purpose of this study is to explain how the City Apparatus Work Unit is related to controlling the arrangement of minimarkets in the city of Surabaya. This study uses Ricky W. Griffin's theory of control measures or Levels of Control about four steps in control, namely: establishing standards, measuring performance, comparing performance against standards, and considering corrective action. The research method used is a qualitative research method that aims to understand, analyze, and explain the aspects that exist in controlling the arrangement of minimarkets in the city of Surabaya. Data collection techniques are carried out by means, observation, interviews and documents. And to validate the data the authors used the source triangulation technique. The results of this study show that the control of minimarket arrangement in Surabaya City has not run in accordance with applicable regulations. Violations that occur range from licensing problems, to spatial planning discrepancies. In addition, there is supervision that is not followed by reports. Until there is still weak enforcement against violating minimarkets. Although there is a Moratorium Letter, the Moratorium Letter is not a solution to minimarket violations in the city of Surabaya. Because the Moratorium Letter only solves the problem of issuing new minimarket permits in the city of Surabaya.